The autonomic control and functional significance of the changes in heart rate associated with air breathing in the jeju, Hoplerythrinus unitaeniatus - McKenzie, D. J.; Campbell, H. A.; Taylor, E. W.; Micheli, M.; Rantin, F. T.; Abe, Augusto Shinya [UNESP] (Company of Biologists Ltd, 2007)
The jeju is a teleost fish with bimodal respiration that utilizes a modified swim bladder as an air-breathing organ (ABO). Like all air-breathing fish studied to date, jeju exhibit pronounced changes in heart rate (f(H)) during air-breathing events, and it is believed that these may facilitate oxygen uptake (M-O2) from the ABO. The current study employed power spectral analysis (PSA) of f(H) patterns, coupled with instantaneous respirometry, to investigate the autonomic control of these phenomena and their functional significance for the efficacy of air breathing. The jeju obtained less than 5% of total M-O2 (M-tO2) from air breathing in normoxia at 26 degrees C, and PSA of beat-to-beat variability in fH revealed a pattern similar to that of unimodal water-breathing fish. In deep aquatic hypoxia (water P-O2=1 kPa) the jeju increased the frequency of air breathing (f(AB)) tenfold and maintained M-tO2 unchanged from normoxia. This was associated with a significant increase in heart rate variability (HRV), each air breath (AB) being preceded by a brief bradycardia and then followed by a brief tachycardia. These f(H) changes are qualitatively similar to those associated with breathing in unimodal air-breathing vertebrates. Within 20 heartbeats after the AB, however, a beat-to-beat variability in f(H) typical of water-breathing fish was re-established. Pharmacological blockade revealed that both adrenergic and cholinergic tone increased simultaneously prior to each AB, and then decreased after it. However, modulation of inhibitory cholinergic tone was responsible for the major proportion of HRV, including the precise beat-to-beat modulation of f(H) around each AB. Pharmacological blockade of all variations in f(H) associated with air breathing in deep hypoxia did not, however, have a significant effect upon f(AB) or the regulation of M-tO2. Thus, the functional significance of the profound HRV during air breathing remains a mystery.
Keywords: air breathing; heart rate variability; teleost